Risk-Based Selection in Unemployment Insurance: Evidence and Implications - Landais, Camille; Nekoei, Arash; Nilsson, Peter; Seim, David; Spinnewijn, Johannes (American Economic Review, 2021)
This paper studies whether adverse selection can rationalize a universal mandate for unemployment insurance (UI). Building on a unique feature of the unemployment policy in Sweden, where workers can opt for supplemental UI coverage above a minimum mandate, we provide the first direct evidence for adverse selection in UI and derive its implications for UI design. We find that the unemployment risk is more than twice as high for workers who buy supplemental coverage. Exploiting variation in risk and prices, we show how 25–30 percent of this correlation is driven by risk-based selection, with the remainder driven by moral hazard. Due to the moral hazard and despite the adverse selection we find that mandating the supplemental coverage to individuals with low willingness-to-pay would be suboptimal. We show under which conditions a design leaving choice to workers would dominate a UI system with a single mandate. In this design, using a subsidy for supplemental coverage is optimal and complementary to the use of a minimum mandate. (JEL D82, G22, J65)